THU0047 Matrixins, cytokines and adhesive immunoglobulins within osteoarthritic joint. (1st June 2001) - ?tovickova, J; Hulejova, H; Pesakova, V; Adam, M
Abstract : Research: Centrum, Institute of Rheumatology, Prague, Czech Republic Background: The most abundant joint disease is osteoarthritis. Recently it was classified as cartilagenous, synovial or osseous but the unique forms may be combined. The main feature of the disease is imbalance between synthetic and degradative processes within joint tissues. Executive part in degradative processes play matrix metalloproteinases, so called matrixins. In situ, they are induced by many stimuli, namely by cytokines and by interaction of different adhesive molecules with their ligands. Having been secreted into the extracellular space, they are activated by serine proteinases, or by other matrixins and inhibited by tissue inhibitors of matrix metalloproteinases, TIMPs. Objectives: In the sera of OA patients we found matrixins MMP-9, MMP-2 and MMP-3 and TIMP-1 together with cytokines IL-8 and TNFα and adhesive molecules ICAM-1 and VCAM-1. To distinguish between the forms of osteoarthritis, we search for these molecules in all joint tissues that is in cartilage, synovium, granulous tissue within subchondral bone, synovial fluid and blood serum. The joint tissues and fluids we obtained from surgery during total hip or knee replacement. Methods: The joint tissues were derived from 22 patients. The patients were 17 female and 6 male, 67, 5 ± 9, 6 years old. The metalloproteinase spectrum in the body fluids and extracts of joint tissues were evaluated by zymography. The concentration of metalloproteinases and TIMP-1 were assessed by ELISA (Biotrak, Amersham Pharmacia Biotech), the concentration of adhesive immunoglobulins by Bender ELISA (MedSystems Diagnostics GmbH), and the concentration of IL-8 and TNFα were determined on Immulite (DPC, USA). Results: We found that the most abundant matrixine within cartilage and synovium is either gelatinase A (MMP-2) or stromelysine-1 (MMP-3). On the other hand, within granulous tissue, blood sera and synovial fluid, the prevailing matrixine is gelatinase B or stromelysine-1. In cartilage, synovial fluid and blood serum TIMP-1 is abundant over sum of matrixins, whereas in synovium and granulous tissue the sum of matrixins is abundant over TIMP-1. There is about 2 to 10 times greater concentration of IL-8 in the cartilage than in other joint compartments. We found significant correlation between levels of sICAM-1 and sVCAM-1; between TNFα and MMP-3, TIMP-1, sICAM-1, sVCAM-1, and IL-8; and between IL-8 and sICAM-1 in all solid joint tissues. In the synovial fluid and blood serum the correlation was less pronounced. Conclusion: There is a great degradative potential within all compartments of osteoarthritic joint due to presence of matrixins, namely that of stromelysin-1. Within cartilage and synovial fluid the proteolytic potential is equilibrated by TIMP-1 whereas within synovium and granulous tissue is not. Synovium and granulous tissue are highly probably the propellers of degradative process in osteoarthritis. Reference: Yoshihara Y, et al . Matrix metalloproteinases and tissue inhibitors of metalloproteinases in synovial fluids from patients with rheumatoid arthritis or osteoarthritis. Ann Rheum Dis. 2000;59:455–61